Pressuposição : diferentes abordagens teóricas e suas consequências para o ensino de graduação em Letras - Soares, Verônica de Fátima Camargo (2012)
This is a research on the presupposition in Modern Linguistics, which serves as a principle for studies under different perspectives, such as Logical-Philosophical, Semanticist, Pragmaticist and Discourse. It goes through a theoretical path that begins in Frege (1982), one of the first scholars to theorize about this issue, whose perspective is logical, and also through Ducrot (1977, 1981, 1987), our theoretical base, the author theorized about linguistic presupposition the most, whose structuralist perspective is focused on enunciatively questions; reaching a pragmaticist look for the presupposition through the theoretical contributions of Austin (1990). The main objectives of this paper are first to discuss whether such approaches on the presupposition are conflicting to the point of compromising the teaching at the undergraduate level in Letters. Therefore, we analyzed whether there are convergences among the theories studied that are able to sustain an approach about the presupposition as a linguistic phenomenon, and after that, by examining the presuppositions which are presented in the textbooks devoted to the teaching of Letters graduation, aiming to verify the theoretical and methodological approach on the subject by the authors" perspective. Our hypothesis is that the theoretical approaches on presupposition are deeply divergent, what would allow the emergence of different meanings to it, according to the selected approach; it would also make fluid the concept of presupposition. In order to illustrate the presence of this theme in the majoring in Letters formation, we observed the treatment given to the presupposition on the “National Examination of Courses” (Provão) and “National Examination of Student Performance” (ENADE), prepared by the MEC, whose purpose is to test the academic knowledge. The conclusion is that presupposition as linguistic phenomenon needs more research due to lack of sufficient evidences to support its application in the training of professionals of Letters currently.